Falling in love ebook - Leon, Donna (Commissario Brunetti, 2015)
An opera singer is terrified by an obsessive fan in this “stunning” mystery in the New York Times –bestselling series set in Venice, Italy ( Library Journal, starred review).   Years ago, Guido Brunetti cleared the opera star Flavia Petrelli in the murder of a renowned conductor. Now the soprano is returning to Venice—and its celebrated opera house, La Fenice—to sing the lead in Tosca .   Brunetti and his wife, Paola, attend an early performance, and Flavia receives a standing ovation. Back in her dressing room, she finds bouquets of yellow roses—too many roses. Every surface of the room is covered with them. An anonymous fan has been showering Flavia with these beautiful gifts in London, St. Petersburg, Amsterdam, and now Venice, but she no longer feels flattered, only frightened.   When she confesses her alarm—and then a singer who has caught Flavia’s attention is savagely attacked—Brunetti begins to think that Flavia’s fears are justified in ways neither of them imagined, and he must enter into the psyche of an obsessive fan . . .   From a New York Times –bestselling and Silver Dagger Award–winning author, this is “one of the most exquisite and subtle detective series ever” ( The Washington Post ).   “Another provocative addition to a fine series, certain to appeal to aficionados of profound literary mysteries such as Louise Penny’s  How the Light Gets In .” — Library Journal , starred review